Caracterización físico-química de la placenta de cacao nacional y ccn-51 de la provincia de El Oro - Toro Castillo, Brenda Silvana (My University, 2024)
The present study focuses on the physicochemical characterization of the placenta of Nacional and CCN-51 cacao from the province of El Oro, Ecuador. Using UV-vis spectrophotometry, the levels of total polyphenols, reducing sugars and vitamin C were analyzed in samples collected from five different locations. The results revealed significant variations in the levels of these bioactive compounds according to the locality of origin, with Atahualpa and El Guabo standing out for their high levels of sugars and vitamin C, respectively. In addition, it was observed that CCN-51 has higher concentrations of sugars and polyphenols compared to Nacional cocoa, while the latter contains more vitamin C. The research also highlights the influence of climatic and geographical conditions on the physicochemical composition of cocoa placenta, which has important implications for its industrial utilization. The high contents of antioxidant compounds in cocoa placenta position it as a valuable source for the cosmetic and pharmaceutical industry, as well as for the development of nutritional supplements and food products. Statistical analyses validated the accuracy and reliability of the data obtained, with high coefficients of determination (R²) for all parameters analyzed. This supports the robustness of the findings and their potential application in future research and industrial settings. The study suggests the need to explore and develop new products incorporating cocoa placenta extracts, optimize agricultural practices according to geographical and climatic conditions, and promote sustainable practices in the cocoa industry. Furthermore, it is recommended that the study be extended to other regions and that additional research be conducted on the functional properties and health benefits of the bioactive compounds present in the cocoa placenta.
El presente estudio se enfoca en la caracterización fisicoquímica de la placenta de cacao Nacional y CCN-51 de la provincia de El Oro, Ecuador. Mediante el uso de espectrofotometría UV-vis, se analizaron los niveles de polifenoles totales, azúcares reductores y vitamina C en muestras recolectadas de cinco localidades distintas. Los resultados revelaron variaciones significativas en los niveles de estos compuestos bioactivos según la localidad de origen, destacándose Atahualpa y El Guabo por sus altos niveles de azúcares y vitamina C, respectivamente. Además, se observó que el CCN-51 presenta mayores concentraciones de azúcares y polifenoles en comparación con el cacao Nacional, mientras que este último contiene más vitamina C. La investigación también subraya la influencia de las condiciones climáticas y geográficas en la composición fisicoquímica de la placenta de cacao, lo que tiene implicaciones importantes para su aprovechamiento industrial. Los altos contenidos de compuestos antioxidantes en la placenta de cacao la posicionan como una fuente valiosa en diferentes industrias como son: Química y Farmacéutica, además, para el desarrollo de suplementos nutricionales y productos alimentarios. Los análisis estadísticos validaron la precisión, así como también, la fiabilidad de los datos obtenidos, con coeficientes de determinación (R²) elevados para todos los parámetros analizados. Esto respalda la robustez de los hallazgos y su potencial aplicación en futuras investigaciones y en el ámbito industrial. El estudio sugiere la necesidad de explorar y desarrollar nuevos productos que incorporen extractos de placenta de cacao, optimizar las prácticas agrícolas según las condiciones geográficas y climáticas, y promover prácticas sostenibles en la industria del cacao. Además, se recomienda la ampliación del estudio a otras regiones y la realización de investigaciones adicionales sobre las propiedades funcionales y también acerca de los beneficios para la salud de los compuestos bioactivos presentes en la placenta de cacao.
Keywords: PLACENTA DE CACAO; POLIFENOLES; VITAMINA C; AZUCARES